PROPERTIES OF CONCRETE MADE OF TERNARY CEMENTITIOUS SYSTEM - Siregar, Atur Parhorasan Nusantara (Jurnal Teknik Sipil, 2018)
Utilising industrial waste materials containing pozolanic compounds has been widely investigated for cement replacement. Fly ash and microslilica are materials having significant pozolanic compounds and can be used to create ternary cementitious system. Slump of fresh concrete, porosity and compressive strength of hardened concrete were parametric study investigated in this study of ternary cementitious system.  Three types of concrete mixtures, i.e. concrete mixture using original portland cement (OPC) as normal concrete, OPC-fly ash-microslica without superplasticiser, and OPC-fly ash-microslica with additional superplasticiser have been investigated. Fresh concrete using fly ash and microslilica demonstrated having higher slump and lower porosity than normal concrete. Compressive strength of concrete using fly ash and microsilica were higher than normal concrete. Utilising fly ash and microsilica as ternary cementitious system was found to have beneficial effect on fresh concrete, compressive strength and porosity of hardened concrete.